2021
DOI: 10.3389/fgene.2021.656545
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Genetic Overlap Between Rheumatoid Arthritis and Systemic Lupus Erythematosus Using GWAS Summary Statistics

Abstract: BackgroundClinical and epidemiological studies have suggested systemic lupus erythematosus (SLE) and rheumatoid arthritis (RA) are comorbidities and common genetic etiologies can partly explain such coexistence. However, shared genetic determinations underlying the two diseases remain largely unknown.MethodsOur analysis relied on summary statistics available from genome-wide association studies of SLE (N = 23,210) and RA (N = 58,284). We first evaluated the genetic correlation between RA and SLE through the li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 105 publications
0
12
0
Order By: Relevance
“…Previous GWASs have demonstrated that several SNPs are associated with both RA and SLE [ 31 ]. For example, rs7574865 in STAT4 and rs2476601 in PTPN22 are well-known genetic variants associated with both diseases [ 32 , 33 ].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Previous GWASs have demonstrated that several SNPs are associated with both RA and SLE [ 31 ]. For example, rs7574865 in STAT4 and rs2476601 in PTPN22 are well-known genetic variants associated with both diseases [ 32 , 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…For example, rs7574865 in STAT4 and rs2476601 in PTPN22 are well-known genetic variants associated with both diseases [ 32 , 33 ]. In patients with RA, rs6457617 and rs9275406 in HLA-DQA1; rs9275406 and rs12525220 in HLA-DQB1; and rs6457620, rs615672, rs7765379, rs660895, rs13192471, rs6910071, rs9268839, rs9271348, rs3104413, rs9269234, rs9268839 and rs112112734 in HLA-DRB1 were common genetic loci [ 31 ]. Previous studies had reported rs2647012 and rs2187668 in HLA-DQA1; rs3129716 and rs114092478 in HLA DQB1; and rs9271100, rs9270984, and rs3135394 in HLA DRB1 to be associated with SLE [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations